Country Economic Memorandum for Sao Tome and Principe - Background Note 11 : What is the Potential and Hindrances for the Tourism Sector in Sao Tome and Príncipe? - Monte-Rojas, Gabriel (World Bank, Washington, DC, 2019)
The purpose of this paper is to empirically evaluate the tourism performance of STP with respect to the main determinants that have been found in the literature. Tourism is clearly a comparative advantage of STP and already an important economic activity, however, STP is far from the characterization of a tourism-dependent small economy. Tourism represents 10.8 percent of GDP and the ratio between international inbound tourists and population is at 14.5 percent. For a summary of how STP relates to other destinations. This puts STP as the twelfth country in terms of size of direct contribution of the tourism sector to GDP and the eighteenth in terms of the ratio between tourists and population. Using data from different sources, this note analyzes STP’s tourism-related characteristics and uses different empirical tools to evaluate them vis-à-vis its peers. Economic literature shows that tourism demand is affected by price and income but also by a host of other factors such as air connectivity, language, and culture among others. First, there is an extensive research agenda on measuring price and income elasticities of tourism, which is specific for different types of tourism destination. Second, there is a myriad of characteristics that are found to be important to the tourism industry, such as remoteness, language, culture, air connectivity, bilateral trade, etc. More recently, there has been many studies emphasizing the role of digital media and digital presence1 as a key determinant of tourist decisions.